2016
DOI: 10.1007/s00726-016-2355-4
|View full text |Cite
|
Sign up to set email alerts
|

Dietary protein supplementation in the elderly for limiting muscle mass loss

Abstract: Supplementation with whey and other dietary protein, mainly associated with exercise training, has been proposed to be beneficial for the elderly to gain and maintain lean body mass and improve health parameters. The main objective of this review is to examine the evidence provided by the scientific literature indicating benefit from such supplementation and to define the likely best strategy of protein uptake for optimal objectified results in the elderly. Overall, it appears that an intake of approximately 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(30 citation statements)
references
References 158 publications
1
28
0
1
Order By: Relevance
“…FranSO indicated a sole effect of protein supplementation, even when no exercise was performed. Having said that, it has to be taken into account that in respective trial, an amount above the recommended protein intake (1.7 versus 1.2-1.6 g/kg/day 25,58 ) had been prescribed and this amount of 1.7 g/kg/day was furthermore a much higher amount of consumed protein by the non-exercise CG than in FrOST, in which the non-exercise CG only received 1.2 kg/d. Looking at the positive effect of mere supplementation in the FranSO non-exercise CG as opposed to the lack of effect of supplementation in our trial's non-exercise CG raises the question, whether what is considered an adequate protein intake for the elderly, is actually sufficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…FranSO indicated a sole effect of protein supplementation, even when no exercise was performed. Having said that, it has to be taken into account that in respective trial, an amount above the recommended protein intake (1.7 versus 1.2-1.6 g/kg/day 25,58 ) had been prescribed and this amount of 1.7 g/kg/day was furthermore a much higher amount of consumed protein by the non-exercise CG than in FrOST, in which the non-exercise CG only received 1.2 kg/d. Looking at the positive effect of mere supplementation in the FranSO non-exercise CG as opposed to the lack of effect of supplementation in our trial's non-exercise CG raises the question, whether what is considered an adequate protein intake for the elderly, is actually sufficient.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis by Morton et al contradicts additional effects of higher protein consumption than 1,6 g/kg/day, 63 and discussions on general effectivity of protein supplementation continue, but there are strong arguments speaking for an increased intake, too. 58,[63][64][65][66][67][68] Nevertheless, the possible adverse effects of higher protein intake on kidney and colon health cannot be neglected. 58 Thus, an optimized balance between not too low, but safe enough has to be aimed for.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, previous research suggests that protein intakes are significantly reduced at the breakfast meal with intakes of ~10 g (Tieland et al 2012a). These lower levels of protein are not considered optimum for maximisation of muscle protein synthesis for our study population, who should be receiving at least 25-30 g of protein per meal (Moore et al 2014;Phillips 2015;Lancha Jr et al 2016) based on their body mass. Thirty grams of high quality protein per meal would in turn provide approximately 15 g of EAAs (Hulmi et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, evidence supports an increase in daily protein intake from the current RDA (0.8 g•kg -1 •d -1 ) to 1.0-1.6 g•kg -1 •d -1 (Bauer et al 2013;Deutz et al 2014;Loenneke et al 2016;Traylor et al 2018). Consumption of at least 0.4 g•kg -1 •BM of high quality protein per meal (Moore et al 2014;Phillips 2015;Lancha Jr et al 2016) is also recommended. This is primarily due to their high essential amino acid (EAA) content which optimises muscle protein synthesis (Breen et al 2011;Churchward-Venne et al 2014;Paddon-Jones et al 2014;Xu et al 2015;Murphy et al 2016;Phillips 2016;Hamarsland et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Adequate calorie, protein and vitamin intake is essential to preserve muscle mass and strength during the ageing process [20]. Approximately 1.5 g protein/kg of body weight/day is recommended for the older population, considering potential anabolic resistance; however, maximum protein intake without adverse effects is not known, so recommendations must be individualized [21]. A meta-analysis of 15 controlled trials revealed that protein or essential amino acid supplementation did not significantly increase the effects of resistance exercise training on muscle mass, strength and functionality [22].…”
Section: Discussionmentioning
confidence: 99%